Using sprinklers to improve performance of heat-stressed feedlot cattle - Ames, D.R.; Robinson, J.B.; Nichols, David A. (Kansas State University. Agricultural Experiment Station, 2011)
During a 56-day test, four pens of finishing cattle were sprinkled when dry-bulb temperatures exceeded 80 F. The performance of the cattle was compared with that of cattle in pens not sprinkled. Cattle in sprinkled pens gained faster (2.83 vs 2.44 lbs per day, P<.05) and more efficiently (4.45 vs 5.20 lbs feed per lb gain) than did those in the nonsprinkled. Feed intakes of all cattle were similar.
Keywords: Beef; Performance; Heat-stress; Feedlot